2012
DOI: 10.1002/dys.1437
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Letter‐String Processing in Developmental Dyslexia: What Visual‐to‐Phonology Code Mapping Disorder?

Abstract: Poor parallel letter-string processing in developmental dyslexia was taken as evidence of poor visual attention (VA) span, that is, a limitation of visual attentional resources that affects multi-character processing. However, the use of letter stimuli in oral report tasks was challenged on its capacity to highlight a VA span disorder. In particular, report of poor letter/digit-string processing but preserved symbol-string processing was viewed as evidence of poor visual-to-phonology code mapping, in line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 51 publications
2
47
1
1
Order By: Relevance
“…In a CA-matched design, children with dyslexia showed reduced visual spans for letters and digits. However, their performance was identical to that of CA-matched controls for unfamiliar symbols 40 and coloured dots 44 . Hence, despite their reading difficulty and reduced reading experience, French children with dyslexia showed preserved visual spans for materials that had not been recoded to sound with the same frequency as letters and digits.…”
Section: Impairments In Visual Attentionmentioning
confidence: 51%
“…In a CA-matched design, children with dyslexia showed reduced visual spans for letters and digits. However, their performance was identical to that of CA-matched controls for unfamiliar symbols 40 and coloured dots 44 . Hence, despite their reading difficulty and reduced reading experience, French children with dyslexia showed preserved visual spans for materials that had not been recoded to sound with the same frequency as letters and digits.…”
Section: Impairments In Visual Attentionmentioning
confidence: 51%
“…A series of studies were carried out to support the visual attentional interpretation of the VA span disorder in developmental dyslexia (Lassus-Sangosse et al, 2008; Valdois et al, 2012). Critical arguments were derived from behavioral studies showing that VA span impaired children with developmental dyslexia were similarly impaired in non-verbal tasks requiring multiple non-verbal stimuli processing (Lobier et al, 2012a,b) and from neuroimaging studies showing that the VA span disorder related to underactivation of visual-attention-related parietal regions (namely the superior parietal lobules bilaterally; Peyrin et al, 2011, 2012; Reilhac et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that dyslexic children with a small VA span performed as the matched controls. Other studies provided evidence indicating that articulatory suppression affected the performance in the global report task very slightly (Valdois et al, 2012b). Recent dyslexic data also revealed that the concept of VA span extends to non-verbal material and non-verbal tasks (Lobier et al, 2012).…”
Section: Control Variablesmentioning
confidence: 96%
“…None of the letter clusters in the consonant strings corresponded to complex graphemes in French (e.g., TH or GN) and none of the five consonants matched the skeleton of a real word (e.g., FLMBR for ''FLAMBER''). The performance in this task does not reflect a verbal short-term memory load (LassusSangosse, N'Guyen-Morel, & Valdois, 2008) and is not affected by concurrent articulation (Valdois, Lassus-Sangosse, & Lobier, 2012b) suggesting that it is not modulated by online verbal encoding skills. However, as these tasks use verbal stimuli and need a verbal response, it has been argued that they do not measure visual attention processing but verbal phonological code mapping (e.g., Ziegler, Pech-Georgel, Dufau, & Grainger, 2010).…”
mentioning
confidence: 95%